2006
DOI: 10.1124/jpet.106.109371
|View full text |Cite
|
Sign up to set email alerts
|

System B0,+and the Transport of Thiol-S-Conjugates of Methylmercury

Abstract: Methylmercury (CH 3 Hgϩ ) is a clinically relevant toxicant that is the most abundant form of mercury found in the environment. After exposure, it accumulates in the kidneys, liver, and central nervous system. The mechanisms by which this toxicant is taken up by target cells are only now beginning to be understood. Some experimental data support a hypothesis involving molecular mimicry, whereby thiol conjugates of methylmercury (especially a cysteine S-conjugate) mimic one or more amino acids and are transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…HgCl 2 and methylmercury are the most common forms of mercury to which humans are exposed [4,[6][7]; mersalyl has been used as a prototypal hydrophilic mercury compound which is frequently used as a specific reagent for Cys residues of proteins [35]. Preliminary studies performed with hydrophilic SH reagents, suggested that the reconstituted transporter contains thiol groups of cysteine exposed towards the extraliposomal compartment, which corresponds to the extracellular environment; these data correlated well with the predicted hydropathy profile of ASCT2 [27,40].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…HgCl 2 and methylmercury are the most common forms of mercury to which humans are exposed [4,[6][7]; mersalyl has been used as a prototypal hydrophilic mercury compound which is frequently used as a specific reagent for Cys residues of proteins [35]. Preliminary studies performed with hydrophilic SH reagents, suggested that the reconstituted transporter contains thiol groups of cysteine exposed towards the extraliposomal compartment, which corresponds to the extracellular environment; these data correlated well with the predicted hydropathy profile of ASCT2 [27,40].…”
Section: Discussionmentioning
confidence: 99%
“…14 Differently from other amino acid or anion transporters [2,5,[7][8][9] ASCT2 is not involved in the absorption of mercurials nor as free molecules neither as conjugates. M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 …”
Section: Page 13 Of 30mentioning
confidence: 99%
See 3 more Smart Citations